Synthesis, crystal structure and Hirshfeld analysis of a novel supramolecular compound [Co(tsc)3]2[Co(cit)2](NO3)4·4H2O - Nuralieva, Guzal; Umirzakova, Oydinoy; Torambetov, Batirbay; Rasulov, Abdusamat; Ashurov, Jamshid; Kadirova, Shakhnoza (Acta Crystallographica Section E-Crystallographic Communications, 2025)
A new cobalt complex, bis[tris(aminothiourea)cobalt(III)] bis[2-(carboxymethyl)-2-hydroxybutanedioato]cobalt(II) tetranitrate tetrahydrate, [Co(CH5N3S)3][Co(C6H6O7)2]0.5(NO3)2·2H2O, designated as [Co(tsc)3]2[Co(cit)2](NO3)4·4H2O, was synthesized. Two crystallographically independent cobalt centers are present. In the first, the central metal atom is chelated by three thiosemicarbazide ligands in a bidentate fashion whereas the second, positioned on a crystallographic inversion center, is hexacoordinated by two citrate anions in a distorted octahedral geometry. Additionally, two water molecules and two nitrate anions are present in the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Asymmetric_unit" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">asymmetric unit. Hirshfeld surface analysis revealed that the presence of numerous donor and acceptor groups in the complex, which facilitate hydrogen-bonding interactions that contribute significantly to the overall cohesion of the crystal structure.